1997
DOI: 10.1136/vr.141.14.360
|View full text |Cite
|
Sign up to set email alerts
|

Canine monocytic ehrlichiosis: a retrospective study of 100 cases, and an epidemiological investigation of prognostic indicators for the disease

Abstract: One hundred cases of monocytic ehrlichiosis diagnosed in Israeli dogs were confirmed by the presence of anti-Ehrlichia canis indirect immunofluorescent antibody titres greater than 1:40. The disease occurred in all age groups and there was no sex predilection. German shepherd dogs were significantly over-represented whereas crossbreed dogs were significantly under-represented (P > 0.0005). The most common clinical signs were depression, lethargy, lymphadenomegaly, fever, anorexia, panting, pale mucous membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
83
2
24

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 4 publications
13
83
2
24
Order By: Relevance
“…In contrast Sainz et al (1996), Harrus et al (1997) and Hernandez et al (2004) could not find any sex predilection. Harrus et al (1997) observed a season predilection for ehrlichiosis between May and October. In our study the majority of the dogs had antibodies against Ehrlichia in autumn, presumably associated with the seasonal activity of the vector (Rhipicephalus sanguineus).…”
Section: Ehrlichia Canismentioning
confidence: 49%
See 1 more Smart Citation
“…In contrast Sainz et al (1996), Harrus et al (1997) and Hernandez et al (2004) could not find any sex predilection. Harrus et al (1997) observed a season predilection for ehrlichiosis between May and October. In our study the majority of the dogs had antibodies against Ehrlichia in autumn, presumably associated with the seasonal activity of the vector (Rhipicephalus sanguineus).…”
Section: Ehrlichia Canismentioning
confidence: 49%
“…The difference in hormone level and inherent immune response could be the reason for the gender susceptibility (Klein 2004). In contrast Sainz et al (1996), Harrus et al (1997) and Hernandez et al (2004) could not find any sex predilection. Harrus et al (1997) observed a season predilection for ehrlichiosis between May and October.…”
Section: Ehrlichia Canismentioning
confidence: 58%
“…ISSN 0103-846X (impresso) / ISSN 1984-2961 O diagnóstico da erliquiose é baseado na combinação dos sinais clínicos, anormalidades hematológicas, achados citológicos e sorológicos, sendo mais recentemente a reação em cadeia da polimerase incorporada ao plano diagnóstico (NEER; HARRUS, 2006). A observação microscópica de esfregaços sanguíneos submetidos à coloração do tipo Romanowsky é simples, barata e fornece um registro permanente (FRITZ, 2009); no entanto a sua sensibilidade é baixa, em torno de 4 a 5% dos casos na fase aguda (HARRUS et al, 1997;MENESES et al, 2008).…”
Section: Introductionunclassified
“…Dentre os testes sorológicos, a Imunofluorescência Indireta é utilizada no diagnóstico da erliquiose, sendo aplicável tanto para estudos de infecções experimentais quanto epidemiológicos. Os antígenos utilizados são procedentes do cultivo de células infectadas com E. canis, havendo detecção de anticorpos precoces em até sete dias pós-infecção, embora a maioria dos cães se tornam soropositivos após 28 dias da infecção (HARRUS et al, 1997).…”
Section: Introductionunclassified
“…Algunos estudios de ehrlichiosis canina han demostrado una mayor susceptibilidad del perro Pastor Alemán a esta enfermedad en comparación con otras razas (Harrus et al, 1997;Leiva et al, 2005).…”
Section: Introductionunclassified